CRITERIA AND METHODOLOGY FOR EVALUATING POTENTIALLY DANGEROUS PRODUCTION TECHNOLOGIES - Rumyantsev, Vladislav; Sharapova, Tatiana; Hnatyshak, Andriy; Skachkov, Radion (Scientific Journal "Metallurgy", 2024)
The proposed work examines the criteria for evaluating potentially hazardous production technologies on the example of metallurgical production. The main criterion is proposed to use the coefficient of labor protection. To determine the safety of technological processes (BTP), it is necessary to take into account the normative parameters of labor safety BP. Factors affecting the level of labor protection are given. To determine the level of safety of processes, it is advisable to carry out calculations for a certain period of time, during which the technological process proceeds without violating safety standards. Special attention is paid to the safety assessment of technological processes. The main factors affecting the safety of the technological process are analyzed. All devices that do not participate in the technological process are suitable for ensuring the convenience of work and the safety of workers. It has been proven that the optimal way to increase the safety level of technological processes is their mechanization and automation.